Upgrading Produk Dengan Soft Skill Gelas Dilukis - Rosa Nikmatul Fajri (JEPEmas: Jurnal Pengabdian Masyarakat (Bidang Ekonomi), 2026)
Various significant threats overshadow SMEs attempting to enter the global market. These challenges arise from several factors, including destructive price competition among domestic producers despite increasing raw material costs, substantially lower prices offered by similar foreign SMEs, high labor wages, and limited government support.The primary objectives of this community service program can be summarized as follows: (1) minimizing entrepreneurial practices such as underpricing due to the absence of value-added elements in products, (2) increasing the economic value of products, (3) enhancing the skills of entrepreneurs as well as the general community, and (4) targeting the general community because institutional management and facilities are relatively low-cost, as most participants are still at the micro level or in the early stages of business development, thereby requiring minimal or no formal institutional arrangements.The training program was implemented through direct, two-way interaction involving both instructors and participants. The results of the workshop indicate that participants achieved approximately 95% competency, primarily limited to technical skills. However, these competencies only partially fulfill managerial requirements, as becoming an effective manager requires not only proficiency in using tools and adhering to procedures but also the ability to perform specialized activities relevant to their professional roles.